Ab initio investigation of hydrogen-based high T c superconductor that is stable under ambient environment - Zhang, Ting (New journal of physics, 2020)
We report an ab initio investigation of a hydrogen-based high- T c superconductor candidate—crystalized C 4 H 4 in the cubic-gauche ( cg -C 4 H 4 ) structure, with the symmetry of space group I 213 . We find the cg -C 4 H 4 structure to be stable under ambient environment; and the evaluation of the electron-phonon coupling strength indicates that the heavily doped cg -C 4 H 4 can generate superconductivity with a T c ∼ 72 K. The high frequency vibrational modes of hydrogen atoms are found to play an important role in the total electron-phonon interaction strength, and the reduction of structural symmetry compared with graphene further enhances the electron–phonon coupling of the carbon framework. Our investigation illustrates a BCS route to realizing the hydrogen-based high T c superconductivity.